2012
DOI: 10.1177/1059840512438617
|View full text |Cite
|
Sign up to set email alerts
|

Examining Childhood Bullying and Adolescent Suicide

Abstract: Adolescent suicide is a preventable tragedy yet is still the third leading cause of death in young people of age 10-24. Contrary to the idea that childhood bullying is a normal part of growing up or a rite of passage, it is now correlated with adolescent suicidality. An integrative review of the contemporary, extant literature was conducted to examine the following question: Are adolescents who have been involved in childhood bullying or cyberbullying as victim, offender, or victim/offender at greater risk for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 17 publications
1
53
0
2
Order By: Relevance
“…8 While a relatively new field, research thus far suggests that cyberbullying exposure and perpetration are associated with depression, low self-esteem, behavioral problems, and substance abuse. 9 Of additional concern is the potential relationship between cyberbullying and deliberate self-harm. A recent meta-analysis found that, compared with traditional bullying, cyberbullying was more strongly associated with suicidal ideation, although there were insufficient data to evaluate its relationship with suicide attempts.…”
mentioning
confidence: 99%
“…8 While a relatively new field, research thus far suggests that cyberbullying exposure and perpetration are associated with depression, low self-esteem, behavioral problems, and substance abuse. 9 Of additional concern is the potential relationship between cyberbullying and deliberate self-harm. A recent meta-analysis found that, compared with traditional bullying, cyberbullying was more strongly associated with suicidal ideation, although there were insufficient data to evaluate its relationship with suicide attempts.…”
mentioning
confidence: 99%
“…For the fact that the school nurse is not part of the school staff, children can confide in the nurse (Cooper et al 2012). In addition it is important to collaborate with the school staff and parents to prevent bullying…”
Section: Implications For Practicementioning
confidence: 99%
“…The school nurse is in an ideal position to conceptualise steps toward a safe school environment to address bullying (Jacobson et al, 2011). Since the school nurse is not in a disciplinary or academic role, children are more likely to confide in the nurse (Cooper, Clements and Holt, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated literature reviews in The Journal of School Nursing (JOSN) during 2012 used the Melnyk and Fineout-Overholt scale to rate the quality of research about two specific problems. One integrated literature review reported synthesis of published studies, establishing the association of childhood bullying experience as victim, offender, or both and adolescent suicide (Cooper, Clements, & Holt, 2012). Cooper and colleagues make a case for the importance of studies that are not at the highest level (RCT) but that replication of studies that are cross-sectional or longitudinal (Level IV) add to the strength of the evidence.…”
Section: Levels Of Evidencementioning
confidence: 99%